The Role of Toll-Like Receptors in Colorectal Cancer Progression: Evidence for Epithelial to Leucocytic Transition - Luddy, Kimberly A.; Robertson-Tessi, Mark; Tafreshi, Narges K.; Soliman, Hatem; Morse, David L. (Frontiers in Immunology, 2014)
Toll-like receptors (TLRs) are expressed by immune cells, intestinal epithelium, and tumor cells. In the homeostatic setting they help to regulate control over invading pathogens and maintain the epithelial lining of the large and small intestines. Aberrant expression of certain TLRs by tumor cells can induce growth inhibition while others contribute to tumorigenesis and progression. Activation of these TLRs can induce inflammation, tumor cell proliferation, immune evasion, local invasion and distant metastasis. These TLR-influenced behaviors have similarities with properties observed in leucocytes, suggesting that tumors may be hijacking immune programs to become more aggressive. The concept of epithelial-to-leucocytic-transition (ELT) is proposed, akin to epithelial-to-mesenchymal-transition (EMT), in which tumors develop the ability to activate leucocytic traits otherwise inaccessible to epithelial cells. Understanding the mechanisms of ELT could lead to novel therapeutic strategies for inhibiting tumor metastasis.